The Influence Risk Factors of Hypertension at the Community Coverage with the 35-54 years old: A mini study in the Meuraxa Health Community Center, Banda Aceh, Indonesia - Masyudi Masyudi; Evi Dewi Yani; Muhammad Ridhwan; Husna Husna; Teuku Muhammad Rafsanjan (Universitas Serambi Mekkah, 2022)
Through a preliminary study, data obtained that the number of hypertensive patients at the Meuraxa Health Center in Banda Aceh City for 2 (two) years in hypertensive patients in 2014 there were 542 visits and in 2015 there were 787 visits and ranked 1 (first) out of twenty one distributions. disease at the Meuraxa Health Center Banda Aceh. And at the beginning of 2016, January, February and March it was found that the number of visits increased to 249 visits. This study uses an analytical method, using a